The Turn of the Tide: The Story of How Margaret Solved Her Problem - Porter, Eleanor H. (Eleanor Hodgman), 1868-1920; Merrill, Frank T., 1848-1923 (Salt Lake City, UT : Project Gutenberg, 2011)
"The Turn of the Tide: The Story of How Margaret Solved Her Problem" by Eleanor H. Porter is a novel likely written in the early 20th century. The book tells the poignant story of a young girl named Margaret who, after being lost for four years, returns to her mother, Mrs. Kendall, and struggles to adjust to her new life of comfort while grappling with her past in the city slums. The novel explores themes of social class, compassion, and personal growth as Margaret navigates her relationships with those around her. The opening of the novel introduces Margaret, who has just reunited with her mother at their home, Five Oaks, filled with nostalgia and bewilderment. The narrative shows her blissful rediscovery of home and her mother$1 (Bs affection, contrasted with her traumatic memories of her past life marked by hardship and survival. As Margaret shares her experiences and remembers the kindness of those she had to leave behind, her mother grapples with the challenge of integrating her daughter's past into their new life. The reader is drawn into the emotional complexity of their relationship as they both seek to find a balance between gratitude and the urge to help those less fortunate. (This is an automatically generated summary.)s
Release date is 2011-06-12
E-text prepared by Roger Frank and the Online Distributed Proofreading Team (http://www.pgdp.net)
Keywords: Fiction